2019
DOI: 10.1016/j.gaceta.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural adaptation and psychometric properties of Spanish version of Pregnancy Physical Activity Questionnaire: the PregnActive project

Abstract: Spanish version of PPAQ is a brief and easily interpretable questionnaire with good reliability and ability to rank individuals, and poor validity compared with multi-sensor monitor. The use of PPAQ provides information of pregnancy-specific activities in order to establish physical activity levels of pregnant women and adapt health promotion interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…The median for sports/exercise was consistent with the results from other studies, which showed that the amount of energy expended during sports and exercise by pregnant women is relatively modest [ 25 , 35 , 40 , 41 , 42 , 44 , 45 , 48 ]. This could be because the participants in our study group were in the last trimester of pregnancy and were already preparing for childbirth through activities that consumed less energy and through continued daily activities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The median for sports/exercise was consistent with the results from other studies, which showed that the amount of energy expended during sports and exercise by pregnant women is relatively modest [ 25 , 35 , 40 , 41 , 42 , 44 , 45 , 48 ]. This could be because the participants in our study group were in the last trimester of pregnancy and were already preparing for childbirth through activities that consumed less energy and through continued daily activities.…”
Section: Discussionsupporting
confidence: 90%
“…The ICC for occupational activity in our study showed good reliability, as it did in the studies of Chinese, Spanish, Vietnamese, Persians, and Poles [ 34 , 40 , 41 , 42 , 43 ]. In addition, the ICCs for household activity and sports/exercise activity showed good reliability, which was in line with other studies [ 34 , 35 , 40 , 42 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, the increase in MVPA during pregnancy may be difficult due to the increases in basal energy expenditure and the elevated metabolic costs of exercise during pregnancy, which explain women's selection of less‐demanding activities during pregnancy. Therefore, as our results showed, LPA, which accounts for 80% of the pregnant women's time spent in physical activity, may be a good way or a progressive step to reallocate ST, although with lower benefits than those obtained by MVPA. This is an interesting finding because the reallocation involving LPA in others CODA studies did not show this association with health benefits, and as we aforementioned could be explained with the particular characteristics of pregnant women, which could obtain health benefits replacing ST with LPA.…”
Section: Discussionmentioning
confidence: 68%
“…The pregnancy physical activity questionnaire (PPAQ). The version validated for the Spanish population was used in this study [ 32 ]. The PPAQ is a semiquantitative questionnaire that reports the time spent in 32 activities categorized into five categories including household task (13 items), work activities (five items), sports/exercise practices (eight items), transportation (three items) and inactivity (three items) and total activity.…”
Section: Methodsmentioning
confidence: 99%